The Role of Market Orientation in Linking Customer Knowledge, Networking, and Culture to Product Innovation and Success in Batam's F&B Industry - Yuwono, Wisnu; Fortuna, Erica; Suprapto, Yandi (Universitas Yudharta Pasuruan, 2025)
Introduction; MSMEs face serious challenges in facing the industrial revolution 4.0 and the era of society 5.0, where there are changes in tastes, trends and increasingly competitive business competition. This condition requires MSMEs to continue to innovate even though data shows that not all MSMEs have transformed and innovated. This study aims to analyze the influence of customer knowledge, networking and cultural knowledge on product innovation and new product success with market orientation as an intervening. Methods; The research methodology uses a survey technique on 281 respondents of food & beverage MSME actors in Batam City, and the collected data is processed using SmartPLS software version 3.0. Result; The results of the study indicate that there is a significant positive influence of customer knowledge, networking and cultural knowledge variables on product innovation and new product success, and market orientation can mediate the relationship. Conclusion; The results of this study can be a reference for MSME actors in running their businesses to remain competitive in the era of globalization.